PENGARUH KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA PT. MITRA BISNIS KELUARGA VENTURA WILAYAH MALANG (Jurnal Bisnis Indonesia, 2022)
This research aims to determine the effect of leadership and work motivation either partially or simultaneously on employee performance at PT. Mitra Bisnis Keluarga (MBK) Ventura in Malang Region. Employee performance can be improved if the company pays attention to the leadership and work motivation experienced by each employee. A controlled leadership style and level of motivation are able to enable employees to perform their duties and responsibilities properly according to what is directed by the leadership of the company. Besides that, it can also make employees increase the intensity of their performance. The data in this study were analyzed using quantitative methods with a total number of respondents as many as 61 employees and using five formulas, namely Multiple Regression Analysis, Correlation Analysis, T-test, F-Test and Determination Coefficient Test (R2). The results of this study indicate that the variables of leadership and work motivation affect employee performance by 84.6% and 15.4% are influenced by other variables which are not included in this study. Simultaneously and partially show that there is an influence between leadership and work motivation on the performance of employees of PT. Mitra bisnis Keluarga (MBK) of the Malang Region..  DOI : https://doi.org/10.33005/jbi.v13i1.3082